2017
DOI: 10.1503/cmaj.170125
|View full text |Cite
|
Sign up to set email alerts
|

Depression and mortality in a longitudinal study: 1952–2011

Abstract: BACKGROUND:Many studies have shown that depression increases mortality risk. We aimed to investigate the duration of time over which depression is associated with increased risk of mortality, secular trends in the association between depression and mortality, and sex differences in the association between depression and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
133
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 203 publications
(145 citation statements)
references
References 38 publications
7
133
0
5
Order By: Relevance
“…The mortality linkage conducted by Statistics Canada did not cover deaths that were not recorded in Canadian provincial registrars. However, the number of deaths identified by the mortality linkage is consistent with expectations based on applying provincial mortality rates to the age and sex distribution of the sample (Gilman et al, 2017). This study provides further evidence of the mortality burden of depressive symptoms.…”
Section: Associations Of Depression and Anxiety Factors With Mortalitysupporting
confidence: 83%
See 3 more Smart Citations
“…The mortality linkage conducted by Statistics Canada did not cover deaths that were not recorded in Canadian provincial registrars. However, the number of deaths identified by the mortality linkage is consistent with expectations based on applying provincial mortality rates to the age and sex distribution of the sample (Gilman et al, 2017). This study provides further evidence of the mortality burden of depressive symptoms.…”
Section: Associations Of Depression and Anxiety Factors With Mortalitysupporting
confidence: 83%
“…These findings are consistent with previous research suggesting that depression is associated with increased risk of mortality (Cuijpers et al., ), and that this mortality burden is more prominent among males (Cuijpers et al., ; Naicker et al., ). Indeed, previous results from the SCS have indicated that depression is associated with an elevated risk of mortality, especially among males (Gilman et al., ; Murphy et al., ; Murphy et al., ). Psychological distress, including symptoms common to both depression and anxiety, has also been associated with mortality (Russ et al., ), and some research has suggested that this burden, too, is higher among males (Puustinen, Koponen, Kautiainen, Ntyselk, & Vanhala, ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…2015). In particular, Major Depressive Disorder (MDD) has been consistently associated with higher risk of mortality (Cuijpers et al, 2014a), most strongly among men (Colman et al, 2018; Cuijpers et al, 2014b; Gilman et al, 2017). There is less consensus on the relationship between anxiety disorders and mortality.…”
mentioning
confidence: 99%